Carriers Spectra of Functionalized Semiconducting Nanowire and Conformational Transition in Molecules - Lykakh, V.A.; Syrkin, E.S. (Ukrainian Journal of Physics, 2012)
The tuning of the spectrum of semiconducting nanowires as a result of the functionalization by a layer of molecules with a conformational transition is investigated. The situation where the electric charge carrier induces the conformational transition with a change of the orientation of the intrinsic electric dipole moments of molecules is expected. The spectrum of a carrier and the parameters of the arising quantum well are determined by the derived self-consistent system of transcendent equations. The system includes the Schrödinger equation for a charge carrier, nonlinear equations for the intrinsic electric-dipole moments, the material equations de4scribing the interaction of an extra carrier in the nanowire and molecular electric dipoles. In a semiconductor nanowire, the hole and electron spectra are symmetric. It is shown that the layer of adsorbed molecules breaks this symmetry when the molecular dipoles create the conditions for a localization of carriers of only one kind, which depends on the charge sign and the orientation of dipoles. The functionalized nanowires can be used as a semiconductor rectifier.